2010
DOI: 10.1128/jb.00233-09
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Regulation of Toxin-Antitoxin Systems by ClpPC in Staphylococcus aureus

Abstract: Bacterial toxin-antitoxin (TA) systems typically consist of a small, labile antitoxin that inactivates a specific longer-lived toxin. In Escherichia coli, such antitoxins are proteolytically regulated by the ATP-dependent proteases Lon and ClpP. Under normal conditions, antitoxin synthesis is sufficient to replace this loss from proteolysis, and the bacterium remains protected from the toxin. However, if TA production is interrupted, antitoxin levels decrease, and the cognate toxin is free to inhibit the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
113
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 45 publications
3
113
0
Order By: Relevance
“…In Gram-positive bacteria, the chaperones ClpX, ClpC, ClpE, and ClpY interact with the ClpP protease core. In a previous paper, the ClpC chaperone was shown to be essential for the ClpP-mediated degradation of the MazEsa, Axe1, and Axe2 antitoxins in S. aureus, a Gram-positive human pathogen (16). Increased stability of these antitoxins was observed only in S. aureus strains that were deficient for clpC or clpP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Gram-positive bacteria, the chaperones ClpX, ClpC, ClpE, and ClpY interact with the ClpP protease core. In a previous paper, the ClpC chaperone was shown to be essential for the ClpP-mediated degradation of the MazEsa, Axe1, and Axe2 antitoxins in S. aureus, a Gram-positive human pathogen (16). Increased stability of these antitoxins was observed only in S. aureus strains that were deficient for clpC or clpP.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this could be a different proteolytic regulation of this TA system. It was demonstrated for the mazEF system that homologous antidotes were degraded by various proteases in the host strains (12,16), which were also dependent on environmental conditions (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus expresses three intracellular, ATP-dependent proteases, known as ClpP, FtsH, and HslV (ClpQ), that are important for managing protein levels and directing stress responses. The ClpP protease is believed to be the principal degradation machinery in S. aureus, while FtsH and HslV play less critical roles in the bacterial stress response (16)(17)(18)(19). Experiments using strains inactivated for clpP, ftsH, or hslV demonstrated that none of these proteases are responsible for ensuring the heme-dependent stability of IsdG (15).…”
mentioning
confidence: 99%
“…Under favourable growth conditions genes of most TA systems are coexpressed and the deleterious activity of the toxin is prevented by the antitoxin 7 . However, various stress stimuli alter the toxin/antitoxin balance, usually by inducing increased proteolytic degradation of the labile antitoxin [8][9][10] . The activated toxin induces a dormant state or other adaptations that enable the bacteria to survive environmentally unfavourable conditions [11][12][13] .…”
mentioning
confidence: 99%